ABT‐199 (Venetoclax), a BH3‐mimetic Bcl‐2 inhibitor, does not cause Ca2+‐signalling dysregulation or toxicity in pancreatic acinar cells. (8th November 2018) - Jakubowska, Monika A; Kerkhofs, Martijn; Martines, Claudio; Efremov, Dimitar G; Gerasimenko, Julia V; Gerasimenko, Oleg V; Petersen, Ole H; Bultynck, Geert; Vervliet, Tim; Ferdek, Pawel E
Abstract : Background and Purpose: Many cancer cells depend on anti‐apoptotic B‐cell lymphoma 2 (Bcl‐2) proteins for their survival. Bcl‐2 antagonism through Bcl‐2 homology 3 (BH3) mimetics has emerged as a novel anti‐cancer therapy. ABT‐199 (Venetoclax), a recently developed BH3 mimetic that selectively inhibits Bcl‐2, was introduced into the clinic for treatment of relapsed chronic lymphocytic leukaemia. Early generations of Bcl‐2 inhibitors evoked sustained Ca 2+ responses in pancreatic acinar cells (PACs) inducing cell death. Therefore, BH3 mimetics could potentially be toxic for the pancreas when used to treat cancer. Although ABT‐199 was shown to kill Bcl‐2‐dependent cancer cells without affecting intracellular Ca 2+ signalling, its effects on PACs have not yet been determined. Hence, it is essential and timely to assess whether this recently approved anti‐leukaemic drug might potentially have pancreatotoxic effects. Experimental Approach: Single‐cell Ca 2+ measurements and cell death analysis were performed on isolated mouse PACs. Key Results: Inhibition of Bcl‐2 via ABT‐199 did not elicit intracellular Ca 2+ signalling on its own or potentiate Ca 2+ signalling induced by physiological/pathophysiological stimuli in PACs. Although ABT‐199 did not affect cell death in PACs, under conditions that killed ABT‐199‐sensitive cancer cells, cytosolic Ca 2+ extrusion was slightly enhanced in the presence of ABT‐199. In contrast, inhibition of Bcl‐xL potentiated pathophysiological Ca 2+ responses in PACs, without exacerbating cell death. Conclusion and Implications: Our results demonstrate that apart from having a modest effect on cytosolic Ca 2+ extrusion, ABT‐199 does not substantially alter intracellular Ca 2+ homeostasis in normal PACs and should be safe for the pancreas during cancer treatment. Linked Articles: This article is part of a themed section on Mitochondrial Pharmacology: Featured Mechanisms and Approaches for Therapy Translation. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v176.22/issuetoc